Los diarios de Piglia: Recuperación de la gestación de Plata quemada - Daniel Balderston (Cuadernos LIRICO)
This paper examines Los diarios de Emilio Renzi for information about Ricardo Piglia’s research in the late 1960s for the novel Plata quemada that he wouldn’t publish until 1997.